Non‐simultaneous kidney exchange cycles in resource‐restricted countries without non‐directed donation – a prospective single‐center cohort study. (26th February 2021) - Kute, Vivek B.; Patel, Himanshu V.; Modi, Pranjal R.; Rizvi, Syed J.; Shah, Pankaj R.; Engineer, Divyesh P.; Banerjee, Subho; Meshram, Hari Shankar; Butala, Bina P.; Modi, Manisha P.; Gandhi, Shruti; Patel, Ansy H.; et al.
Summary: Recent reports suggest that bridge–donor reneging is rare (1.5%) in non‐simultaneous kidney exchange chains. However, in developing countries, the non‐directed donors who would be needed to initiate chains are unavailable, and furthermore, limited surgical space and resources restrain the feasibility of simultaneous kidney exchange cycles. Therefore, the aim of this study was to evaluate the bridge–donor reneging rate during non‐simultaneous kidney exchange cycles (NSKEC) in a prospective single‐center cohort study ( n  = 67). We describe the protocol used to prepare co‐registered donor–recipient pairs for non‐simultaneous surgeries, in an effort to minimize the reneging rate. In addition, in order to protect any recipients who might be left vulnerable by this arrangement, we proposed the use of standard criteria deceased‐donor kidneys to rectify the injustice in the event of any bridge–donor reneging. We report 17 successful NSKEC resulting in 67 living‐donor kidney transplants (LDKT) using 23 bridge–donors without donor renege and no intervening pairs became unavailable. We propose that NSKEC could increase LDKT, especially for difficult‐to‐match sensitized pairs (25 of our 67 pairs) in countries with limited transplantation resources. Our study confirms that NSKEC can be safely performed with careful patient–donor selection and non‐anonymous kidney exchanges.